Strategic management for hospitality and tourism - Okumus, Fevzi; Altinay, Levent; Chathoth, Prakash; Koseoglu, Mehmet Ali (Routledge, 2020)
"Strategic Management for Hospitality and Tourism is an essential text for both intermediate and advanced learners aspiring to build their knowledge related to the theories and perspectives on the topic. The book provides critical and analytical insights on contemporary theoretical models and management practices while enhancing the learning process through worked examples and cases applied to the hospitality and tourism setting. This new edition highlights the rapidly changing socio-economic and political global landscape and addresses the cultural and socio-economic complexities of hospitality and tourism organizations in the new era. It has been fully updated to include: A new chapter on finance, business ethics, corporate social responsibility, and leadership as well as new content on globalisation, experience economy, crisis management, consumer power, developing service quality, innovation and implementation of principles. New features to aid understanding of the application of theory, and spur critical thinking and decision making. New international case studies with reflective questions throughout the book from both SME's and large-scale businesses. Updated online resources including PowerPoint presentations, additional case studies and exercises, and web links to aid both teaching and learning. Highly illustrated and in full colour design, this book is essential reading for all future hospitality and tourism managers"-- Provided by publisher